Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-2707
|View full text |Cite
|
Sign up to set email alerts
|

Relevance-Based Feature Masking: Improving Neural Network Based Whale Classification Through Explainable Artificial Intelligence

Abstract: Underwater sounds provide essential information for marine researchers to study sea mammals. During long-term studies large amounts of sound signals are being recorded using hydrophones. To facilitate the time consuming process of manually evaluating the recorded data, computational systems are often employed. Recent approaches utilize Convolutional Neural Networks (CNNs) to analyze spectrograms extracted from the audio signal. In this paper we explore the potential of relevance analysis to enhance the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Initially, we intended to use the negative masking algorithm to zero out relevant information and therefore train a network that focuses on different areas than the original Trainer network. This newly created network could then be fused on the decision level with the explanatory network to improve results-an approach that has been successfully used before in a different domain (Schiller et al, 2019). Yet we found that the negative masking approach performed better than the mean masking method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, we intended to use the negative masking algorithm to zero out relevant information and therefore train a network that focuses on different areas than the original Trainer network. This newly created network could then be fused on the decision level with the explanatory network to improve results-an approach that has been successfully used before in a different domain (Schiller et al, 2019). Yet we found that the negative masking approach performed better than the mean masking method.…”
Section: Resultsmentioning
confidence: 99%
“…In this section we present a generic method to assess the relevance of specific areas in the input and integrate this knowledge into a new model during training. Based on previous work from Schiller et al (2019) our approach utilizes saliency maps generated by XAI algorithms like deep Taylor decomposition. These maps aim to identify the parts of the input that were relevant for a specific decision of a neural network.…”
Section: Overview Of Our Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…While a binary map that exactly pinpoints the location of classdiscriminative features in the input is the most desirable and has been found to improve classification performance [28], such accurate maps require human-in-the-loop processing and cannot be readily available for most datasets. Our strategy also differs from feature muting [29] that sets a fixed number of features to zero, which can drastically change sample statistics and risk muting useful features through the fixed threshold. In DFDG, we use SmoothGrad saliency maps [15] to rank the relevance of each observation.…”
Section: Masking Superficial Observationsmentioning
confidence: 99%
“…While such saliency map algorithms are already well established and were even used to improve classification models [15], they are usually developed with experienced machine learning practitioners in mind. This can make the generated explanations difficult to interpret for beginners or users who are unrelated to the field of machine learning.…”
Section: Introductionmentioning
confidence: 99%